1999
DOI: 10.1128/jb.181.6.1728-1732.1999
|View full text |Cite
|
Sign up to set email alerts
|

A Cold Shock-Induced Cyanobacterial RNA Helicase

Abstract: The ability to modify RNA secondary structure is crucial for numerous cellular processes. We have characterized two RNA helicase genes, crhB and crhC, which are differentially expressed in the cyanobacterium Anabaena sp. strain PCC 7120. crhC transcription is limited specifically to cold shock conditions while crhB is expressed under a variety of conditions, including enhanced expression in the cold. This implies that both RNA helicases are involved in the cold acclimation process in cyanobacteria; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…The BC0259 product was annotated in the B. cereus ATCC 14579 genome as an RNA helicase with nine motifs that constitute the conserved helicase core and a DEAD box, revealing that it belongs to the DEAD‐box subgroup of the helicase superfamily 2 (Bleichert & Baserga, 2007). RNA helicases participate in many aspects of RNA metabolism (Silverman et al , 2003) and some have been shown to be cold‐induced (Jones et al , 1996; Chamot et al , 1999; Lim et al , 2000). The 9H2 mutant harbours a transpositional insertion upstream of the BC0259 gene, which reduced BC0259 gene expression during adaptation at 10 °C, but not at 30 °C, as revealed by qRT‐PCR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The BC0259 product was annotated in the B. cereus ATCC 14579 genome as an RNA helicase with nine motifs that constitute the conserved helicase core and a DEAD box, revealing that it belongs to the DEAD‐box subgroup of the helicase superfamily 2 (Bleichert & Baserga, 2007). RNA helicases participate in many aspects of RNA metabolism (Silverman et al , 2003) and some have been shown to be cold‐induced (Jones et al , 1996; Chamot et al , 1999; Lim et al , 2000). The 9H2 mutant harbours a transpositional insertion upstream of the BC0259 gene, which reduced BC0259 gene expression during adaptation at 10 °C, but not at 30 °C, as revealed by qRT‐PCR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their function at regular growth conditions, a number of DEAD‐box helicases have been identified as cold‐shock proteins, implying a physiological role under stress conditions, among them E. coli CsdA, B. subtilis CshA and CshB, M. burtonii DeaD, and Anabaena ChrC . The expression of E. coli CsdA is induced upon cold‐shock .…”
Section: A Possible Physiological Function For Hera?mentioning
confidence: 99%
“…During the cold shock response, it has been noted for a number of bacteria that the expression of RNA-binding proteins is induced (Sato, 1995;Jones et al, 1996;Chamot et al, 1999). It is tempting to speculate that some of these proteins may function in regulating mRNA stability in response to the shift in growth temperature.…”
Section: Rna±protein Interactionsmentioning
confidence: 99%